The impact of cancer: An Italian descriptive study involving 500 long‐term cancer survivors. (10th February 2019) - Muzzatti, Barbara; Gipponi, Katiuscia; Flaiban, Cristiana; Cormio, Claudia; Carnaghi, Carlo; Tralongo, Paolo; Caruso, Michele; Cavina, Raffaele; Tirelli, Umberto; Annunziata, Maria Antonietta
Abstract: Introduction: The well‐being and quality of life (QoL) of long‐term cancer survivors may be affected, both positively and negatively, by psychosocial factors related to the experience of being a cancer patient. We investigated whether, in long‐term cancer survivors, the psychosocial impacts of cancer associate with socio‐demographic–clinical variables; whether, within the positive and negative dimensions taken separately, some impacts are more intense than others; and whether these impacts explain QoL. Methods: Italian long‐term cancer survivors ( n = 500) completed the Impact of Cancer (IOC‐V2) and Short Form 36 Health Survey (SF‐36) questionnaires. Results: The IOC‐V2 negative impact score associated with gender, education, occupational status and health issues, whereas no association was found between the positive impact score and socio‐demographic–clinical variables. Of the positive impacts, Altruism/Empathy was the highest ( p < 0.001); Positive self‐evaluation was higher than Health awareness ( p = 0.001); and Meaning of cancer was the lowest ( p < 0.001). Among the negative impacts, Worry was the highest ( p < 0.001), whereas Body changes concerns was higher than both Appearance concerns ( p < 0.001) and Life Interferences ( p < 0.001). The assessed impacts explained more than 25% of the variance of both physical and mental functioning scores. Conclusions: The provided data document psychosocial factors affecting QoL in Italian long‐term cancer survivors.